2022
DOI: 10.21203/rs.3.rs-1415422/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Removal of Contaminant in Electroplating Waste Water and Its Toxic Effect Using Biosynthesized Silver Nanoparticles

Abstract: The emergence of industries in developing countries is a rising challenge where the generation of undesirable liquid wastes containing pollutants are discharged into water bodies without adequate treatment. This research investigated the removal of contaminant in electroplating wastewater and its toxic effect using biosynthesized silver nanoparticles. Fresh leaves of Piliostigma thonningii were used to synthesize silver nanoparticles (Ag NPs). Dynamic light scattering (DLS), transmission electron microscope (T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…They identified that synthesized gold nanoparticles are spherical and uniformly distributed, with typical sizes of 17.5-23.5 nm (Castillo-López and Pal, 2014). Among the numerous methods for treating wastewater (Christensen et al, 2015), the process using nanoparticles synthesized from peels that oxidize the organic waste completely is a consistent, highly responsive, and economic method (Alharthi et al, 2020;Shittu et al, 2022). Different parts of potatoes have been used for synthesizing the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…They identified that synthesized gold nanoparticles are spherical and uniformly distributed, with typical sizes of 17.5-23.5 nm (Castillo-López and Pal, 2014). Among the numerous methods for treating wastewater (Christensen et al, 2015), the process using nanoparticles synthesized from peels that oxidize the organic waste completely is a consistent, highly responsive, and economic method (Alharthi et al, 2020;Shittu et al, 2022). Different parts of potatoes have been used for synthesizing the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%